Emergence of Raoultella ornithinolytica in human infections from different hospitals in Ecuador with OXA-48-producing resistance - Villacís, José E.; Castelán-Sánchez, Hugo G.; Rojas-Vargas, Jorge; Rodríguez-Cruz, Ulises E.; Albán, Viviana; Reyes, Jorge A.; Meza-Rodríguez, Pablo M.; Dávila-Ramos, Sonia; Villavicencio, Fernando; Galarza, Margarita; Gestal, Monica C. (Frontiers in Microbiology, 2023)
Purpose The purpose of this study was to highlight the clinical and molecular features of 13 Raoultella ornithinolytica strains isolated from clinical environments in Ecuador, and to perform comparative genomics with previously published genomes of Raoultella spp. As Raoultella is primarily found in environmental, clinical settings, we focused our work on identifying mechanisms of resistance that can provide this bacterium an advantage to establish and persist in hospital environments. Methods We analyzed 13 strains of Raoultella ornithinolytica isolated from patients with healthcare associated infections (HAI) in three hospitals in Quito and one in Santo Domingo de Los Tsáchilas, Ecuador, between November 2017 and April 2018. These isolates were subjected to phenotypic antimicrobial susceptibility testing, end-point polymerase chain reaction (PCR) to detect the presence of carbapenemases and whole-genome sequencing. Results Polymerase chain reaction revealed that seven isolates were positive isolates for blaOXA–48 and one for blaKPC–2 gene. Of the seven strains that presented the blaOXA–48 gene, six harbored it on an IncFII plasmid, one was inserted into the bacterial chromosome. The blaKPC gene was detected in an IncM2/IncR plasmid. From the bioinformatics analysis, nine genomes had the gene blaOXA–48, originating from Ecuador. Moreover, all R. ornithinolytica strains contained the ORN-1 gene, which confers resistance for β-lactams, such as penicillins and cephalosporins. Comparative genome analysis of the strains showed that the pangenome of R. ornithinolytica is considered an open pangenome, with 27.77% of core genes, which could be explained by the fact that the antibiotic resistance genes in the ancestral reconstruction are relatively new, suggesting that this genome is constantly incorporating new genes. Conclusion These results reveal the genome plasticity of R. ornithinolytica, particularly in acquiring antibiotic-resistance genes. The genomic surveillance and infectious control of these uncommon species are important since they may contribute to the burden of antimicrobial resistance and human health.